Knowledge mapping of impulsive buying behavior research: a visual analysis using CiteSpace - Gong, Xiyun; Yee, Choy Leong; Lee, Shin Yiing; Ethan Yi, Cao; Abu Naser Mohammad, Saif (Springer Nature, 2024)
With the development of e-commerce, impulse buying behavior has transitioned from offline to online, presenting significant exploration value. This study aims to provide a comprehensive knowledge map and in-depth analysis of research on impulsive purchase behavior, helping readers understand the latest global trends in this field from 1967 to September 30, 2023. The study offers a visual analysis using CiteSpace, encompassing 704 academic articles on impulsive buying behavior published over 55 years. The status is revealed through collaboration networks, co-citation networks, and trend analysis. Researchers explore impulsive buying behavior in various contexts, with “e-commerce” being a primary focus. Notable new keywords include technology, customer satisfaction, perceived value, and virtual reality, among others. These terms contribute to future research directions. Overall, this pioneering research combines visual analysis to provide valuable insights and research recommendations for academics studying impulsive buying behavior.